Just Do It! Self-Determination for Complex Minorities - Dubois, Janique F.
This thesis explores how Indigenous and linguistic communities achieve self-determination without fixed cultural and territorial boundaries. An examination of the governance practices of Métis, Francophones and First Nations in Saskatchewan reveals that these communities use innovative membership and participation rules in lieu of territorial and cultural criteria to delineate the boundaries within which to exercise political power. These practices have allowed territorially dispersed communities to build institutions, adopt laws and deliver services through province-wide governance structures. In addition to providing an empirical basis to support non-territorial models of self-determination, this study offers a new approach to governance that challenges state-centric theories of minority rights by focusing on the transformative power communities generate through stories and actions. PhD